Timeline of diagnosed pain causes in children with severe neurological impairment - Peri, Francesca; Magni, Elena; Pigani, Filippo; Romoli, Raffaella; Vetrella, Simona; De Zen, Lucia; Sagredini, Raffaella; Barbi, Egidio; Cozzi, Giorgio (Frontiers in Pediatrics, 2024)
Objective Pain's causes in children with severe cognitive impairment may be challenging to diagnose. This study aimed to investigate if there is a relationship between pain causes and the age of children. Methods We conducted a multicenter retrospective study in three Italian Pediatric Units. Eligible subjects were patients from 1 to 18 years with severe neurological impairment. We collected data regarding diagnoses, pain causes and medical or surgical procedures. The timing of pain episodes was categorized into age-related periods: infants and toddlers (0–24 months), preschool children (3–5 years), schoolchildren (6–12 years), and adolescents (13–17 years). Results Eighty children with severe neurological impairment were enrolled. The mean age was 11 years (±5.8). Gastroenterological pain was most common in the first years of life (p = 0.004), while orthopaedic and tooth pain was the most typical in schoolchildren and adolescents (p = 0.001 and p = 0.02). Concerning surgical procedures, PEG placement and gastric fundoplication were significantly more common in the first 5 years of age (p = 0.03), and heart surgery was typical of infants (p = 0.04). Orthopaedic surgery was more commonly reported in older children and adolescents (p < 0.001). Conclusions Some causes of pain are more frequent in children with severe neurological impairment in defined age-related periods. Specific age-related pain frequencies may help physicians in the diagnostic approach.